Semi-random and semi-algebraic structural design for IRA-LDPC codes - Li PENG; Qi ZHANG; Bo WANG; Tao CHEN (Tongxin xuebao)
A method of semi-random and semi-algebraic structure was presented for constructing the low-density parity-check matrix that corresponds to the information bits of the IRA codes.Compared with the existing structural LDPC codes,the distinct advantage of the presented compact structural array for information-bit-corresponding matrix is that the position coordinate of each 1 element in this matrix can be calculated by a determinate algebraic expression,which not only reduces the consumption of memory resource for the random parity-check matrix,but also provides the potential probability for designing low complexity hardware circuit of the LDPC encoder/decoder.In addition,compared with the existing practical LDPC codes in industrial standard,the presented IRA-LDPC code is also slight preponderance in the performance of simulation in bit error rate and signal noise ratio (BER-SNB).